Risk factors in body image dissatisfaction: gender, maladaptive perfectionism, and psychological wellbeing. Issue 6 (June 2022) - Hicks, Richard E.; Kenny, Bridget; Stevenson, Simone; Vanstone, Daisy M.
Abstract: Discontent with one's appearance (body image dissatisfaction) has become a global phenomenon, associated with the development of extreme behaviours in order to correct perceived body image problems. Much of the literature has focused on associated destructive behaviours that result from body image dissatisfaction; however, there has been a dearth of research examining risk factors for body image problems in adults. Thus, the current study aimed to investigate risk factors associated with adult body image problems, focusing on two variables highlighted in the literature (gender and maladaptive perfectionism). The current study (1) compared gender differences in body image dissatisfaction and (2) investigated psychological wellbeing as a mediator between maladaptive perfectionism and body image dissatisfaction. The sample included 139 Australian adults from universities (55.7%) and the community (44.3%). Participants completed demographic questions, the Frost Multidimensional Perfectionism Scale, the Psychological Wellbeing questionnaire, the Multidimensional Body-Self Relations Questionnaire, and Marlowe-Crowne Social Desirability Scale. In contrast to predictions, females had higher body area satisfaction and appearance evaluation scores. Furthermore, in line with the hypotheses, psychological wellbeing fully mediated the relationship between maladaptive perfectionism and poor body image. The findings suggest gender, maladaptive perfectionism, and psychological wellbeing may act as risk factors for body image dissatisfaction. Abstract : Maladaptive perfectionism; Wellbeing; Body image dissatisfaction; Body area satisfaction; Appearance evaluation.